Tenjing Sherpa: capstone - Sherpa, Tenjing, artist (Colorado State University. Libraries, 2024)
The artist's statement: My work focuses primarily on analog photography and its experimental potential. I've used film cameras for over three years and have learned many different concepts and ideas that can be used with this medium. I've seen other artists, such as Jerry Uelsmann, who used double exposures to inspire me to dive into experimental printing processes. Creating many different physical prints, I also learned from other photographers, such as Tom Evans and Barbara Murray, to experiment with the film's color composition to create and manipulate the colors. Using these techniques, I was able to make a series that was based on my childhood life. Exploring first the color composition of bright colors abstracting the image, then burning the individual prints with fire to create this burning memory that's stained onto the print and frame.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: photo image making